Studi Korelasi Antara Kecanduan Bermain Game Online Mobile Legends dan Manajemen Waktu dengan Prestasi Akademik Siswa Kelas XI SMA Negeri 1 Kudus Tahun Pelajaran 2020/2021 - Haidar, Wildan Muhammad (Jurnal Empati Bimbingan dan Konseling, 2022)
This research is based on the addiction to playing mobile legend games experienced by high school students. Addiction to mobile legend games is a negative thing, because if someone is addicted to the game, it will be difficult to break away from playing the game. The purpose of this study was to determine the relationship between addiction to playing games, especially mobile legend games and time management with students' academic achievement either partially or simultaneously. This study uses quantitative research methods with the type of ex post facto research. The sample used in this study found 152 of 273 students who were addicted to playing mobile legend games. The sample was found by using purposive sampling and random sampling. The data collection tools used are psychological scales (Gaming Addiction Scale and Time Management Behavior Scale) and documentation (student report cards). as for the data analysis technique using descriptive analysis and multiple correlation analysis. The results showed that there was a significant negative relationship between addiction to playing mobile legend games and students' academic achievement. then there is a significant positive relationship between time management and student academic achievement. Likewise, addiction to playing mobile legend games and time management simultaneously has a strong and significant relationship with academic achievement and has a contribution of 71.5%. Suggestions given to BK teachers or counselors can provide group guidance services or if possible peer counseling can be held in order to reduce addictive behavior in playing mobile legend games, learn to manage so that academic achievement increases.